2007
DOI: 10.1057/palgrave.rlp.5100044
|View full text |Cite
|
Sign up to set email alerts
|

Development of a trip profile for elderly American casino visitors

Abstract: has a PhD in Parks Recreation and Tourism from Michigan State University (2002). The focus of his research is to understand gaming behaviour and casino visitation patterns. He has led various research studies related to gaming and recreation in Michigan. He currently teaches at CHN University in Leewarden, in The Netherlands. Donald F. Holecekis the Director of Travel Tourism and Recreation Resource Center at Michigan State University. The focus of his research is tourism marketing. The centre conducts and spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
1
1
0
1
Order By: Relevance
“…The greatest majority of them preferred one day gaming packages, while the majority of customers ages 21-34 preferred overnight gaming packages. Other research analyzing the data of the casino visitors in the Detroit metro area, by Singh et al (2007), showed similar results. Singh et al (2007) also explained that the reason behind this is because senior customers prefer a peaceful environment, one which has fewer crowds and more machines and seats available, such as is usually found in casinos on weekdays and not weekends, when the casinos are usually filled with younger people.…”
Section: Whatt 14supporting
confidence: 55%
“…The greatest majority of them preferred one day gaming packages, while the majority of customers ages 21-34 preferred overnight gaming packages. Other research analyzing the data of the casino visitors in the Detroit metro area, by Singh et al (2007), showed similar results. Singh et al (2007) also explained that the reason behind this is because senior customers prefer a peaceful environment, one which has fewer crowds and more machines and seats available, such as is usually found in casinos on weekdays and not weekends, when the casinos are usually filled with younger people.…”
Section: Whatt 14supporting
confidence: 55%
“…Previous research brought to marketers' attention the changing needs of an aging population and provided opportunities to understand market segment changes and prepare different market strategies (Moschis et al, 2004;Singh et al, 2007). However, studies of elderly people as a luxury market segment are scarce, even though this population, which is wealthier than other age groups, continues to increase in importance as a market segment in the hospitality business (Gardyn, 2002;Moschis et al, 2004;Singh et al, 2007;Strain et al, 2002).…”
Section: Demographic Characteristics As Indicators Of Attitudes Towarmentioning
confidence: 99%
“…As causas mais importantes são: aposentadoria (Potenza et al, 2006), falta de convívio social (De Brucq e Vital, 2008;Petry e Weiss, 2009), luto pela perda de entes queridos, solidão, reclusão, doenças físicas limitantes e declínio cognitivo (De Brucq e Vital, 2008). Mesmo com essa tendência a jogar mais, os idosos apresentam menor perda financeira com o jogo comparativamente a indivíduos entre 18 e 34 anos de idade (Singh et al, 2007).…”
Section: Jogo Patológicounclassified